Synthesis and Characterization of Pd(II) and Pt(II) Complexes of 2-Pyridyl Methyl Ketazine - Kumar, R.N.; Kumari Chauhan, N.; Das, A.K.; Singh, S.K. (Asian Journal of Chemistry, 2010)
2-Pyridyl methyl ketazine and its Pd(II) and Pt(II) complexes have been prepared and characterized by analytical, IR, magnetic and spectrophotometric studies. The ligand forms dinuclear complexes of the formula [M2(L)2]X4 with bridged tetrafunctional co-ordination of each ligand in the trails configuration.